Traumatic brain injury in a forensic intellectual disability population - Chester, Verity (Psychology, crime & law, 2018)
Traumatic brain injury (TBI) screening in forensic populations has been recommended, due to a high prevalence, links to specific offence profiles and poorer outcomes, such as higher rates of psychiatric disturbance, longer stays in prison, and reoffending. Research focusing on TBI among offenders with intellectual disability (ID) is lacking. This study therefore describes the implementation of TBI screening using the Brain Injury Screening Index (BISI©), TBI prevalence and correlates in a forensic ID service. TBI appeared under recorded in case notes, with considerably more patients self-reporting TBI. Reported causes of TBI differed somewhat to the general population, including childhood physical abuse, self-harming behaviour, and assault. Approximately one-third of injuries did not receive any treatment. Though further adaptations may be required on current screening measures for TBI in offenders with ID, screening can provide valuable information, contributing positively to individual patient therapeutic and risk formulations.